2006
DOI: 10.1051/apido:2006002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of annual and perennial forage mixtures for bumblebees by direct observation and pollen analysis

Abstract: -The value of introduced seed mixtures in providing forage for bumblebees on farmland was assessed by direct observation of individuals and analysis of pollen loads. Two mixtures of perennial grasses and wildflowers were compared with an annual mix of mostly seed-bearing crops over three years. Foraging bees showed contrasting patterns of visitation depending on species. Longer-tongued Bombus species preferred the perennial mixtures in which Trifolium pratense was dominant, whilst shorter-tongued Bombus and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 28 publications
8
88
1
Order By: Relevance
“…Such mixed pollen loads were also found in previous studies, but the degree of pollen mixing in specific bumblebee species varied among studies (Goulson and Darvill 2004;Carvell et al 2006;Leonhardt and Blüthgen 2012;Somme et al 2015) and seems to be predominantly determined by the plant community present at a given site. So, why do individual foragers of nearly all species occasionally mix pollen loads?…”
Section: Discussionsupporting
confidence: 79%
“…Such mixed pollen loads were also found in previous studies, but the degree of pollen mixing in specific bumblebee species varied among studies (Goulson and Darvill 2004;Carvell et al 2006;Leonhardt and Blüthgen 2012;Somme et al 2015) and seems to be predominantly determined by the plant community present at a given site. So, why do individual foragers of nearly all species occasionally mix pollen loads?…”
Section: Discussionsupporting
confidence: 79%
“…(see e.g., Waters et al 2011). Our results on the diet breadth of B. lapidarius in peaty, wet meadows further support the results in agricultural landscapes, as they showed high constancy when foraging for pollen (Carvell et al 2006;Connop et al 2010; Leonhardt and Blüthgen 2 0 1 2 ) . H o w e v e r, s t u d i e s s h o w e d t h a t B. lapidarius can also present diet breadth as large as other co-occurring bumble bee species, or even larger (Goulson and Darvill 2004;Kleijn and Raemakers 2008).…”
Section: Bumble Bee Floral Choicessupporting
confidence: 83%
“…Bumble bee individuals sampled on flowers of Comarum palustre were highly constant during pollen collection. However, as previously shown in other studies (Carvell et al 2006;Goulson and Darvill 2004), differences were observed among bumble bee species in their degree of constancy. Bombus lapidarius and B. pascuorum showed higher constancy than B. terrestris s.l..…”
Section: Bumble Bee Floral Choicessupporting
confidence: 80%
See 1 more Smart Citation
“…Their deep root systems are able to retrieve nutrients from subsoil, thus reducing nitrate leaching, and can sequester C deep in the profile Olmstead and Brummer 2008;Malhi et al 2009). Perennial forages also provide habitat for wildlife, in particular nesting birds and pollinators (Jefferson et al 1999;Carvell et al 2006;Arnold et al 2007).…”
Section: Perennial Crops In Rotationmentioning
confidence: 99%